Glycogen Synthase Kinase 3β Promotes Postoperative Cognitive Dysfunction by Inducing the M1 Polarization and Migration of Microglia - Jingjin Li; Chonglong Shi; Zhengnian Ding; Wenjie Jin (Mediators of Inflammation)
Postoperative cognitive dysfunction (POCD) is a common postoperative central nervous system complication, especially in the elderly. It has been consistently reported that the pathological process of this clinical syndrome is related to neuroinflammation and microglial proliferation. Glycogen synthase kinase 3β (GSK-3β) is a widely expressed kinase with distinct functions in different types of cells. The role of GSK-3β in regulating innate immune activation has been well documented, but as far as we know, its role in POCD has not been fully elucidated. Lithium chloride (LiCl) is a widely used inhibitor of GSK-3β, and it is also the main drug for the treatment of bipolar disorder. Prophylactic administration of lithium chloride (2 mM/kg) can inhibit the expression of proinflammatory mediators in the hippocampus, reduce the hippocampal expression of NF-κB, and increase both the downregulation of M1 microglial-related genes (inducible nitric oxide synthase and CD86) and upregulation of M2 microglial-related genes (IL-10 and CD206), to alleviate the cognitive impairment caused by orthopedic surgery. In vitro, LiCl reversed LPS-induced production of proinflammatory mediators and M1 polarization of microglia. To sum up these results, GSK-3β is a key contributor to POCD and a potential target of neuroprotective strategies.